From LS-PrePost to LS-Dyna an introduction : LS-Dyna for beginners with 13 step by step solved examples - Shah, Qasim H. (LAP Lambert Academic Publishing, 2011)
LS-DYNA is an advanced general-purpose multiphysics simulation software package developed by the Livermore Software Technology Corporation (LSTC). LS-PrePost is an advanced pre and post-processor that is delivered free with LS-DYNA